Asynchronous Upconversion Sampling of Frequency Modulated Combs. Issue 4 (12th February 2023) - Täschler, Philipp; Forrer, Andres; Bertrand, Mathieu; Kapsalidis, Filippos; Beck, Mattias; Faist, Jérôme
Abstract: In recent years, optical frequency combs with a frequency modulated output have attracted considerable attention. While first observed decades ago in externally modulated lasers, a whole class of semiconductor lasers has since been identified to spontaneously enter such a regime of self frequency modulation. However, the temporal properties of these sources could so far only be measured indirectly via phase‐resolved frequency domain measurements. In this work, an asynchronous optical sampling technique which operates directly in time domain is demonstrated. On the basis of a mid‐infrared quantum cascade laser frequency comb, both its instantaneous intensity and optical frequency are measured. The results confirm a quasi‐constant intensity output alongside a close to linear frequency chirp, in accordance with phase‐resolved spectral measurements. Contrary to previous works, stable phase‐locking is achieved in a regime of positive intracavity dispersion resulting in an inversion of the observed frequency modulation. Abstract : An asynchronous optical sampling technique for the temporal characterization of frequency modulated optical frequency combs is introduced in this work. On the basis of a mid‐infrared quantum cascade laser, its instantaneous intensity and optical frequency is measured. The obtained results confirm a quasi‐constant intensity output associated with a close to linear frequency chirp, in accordance with phase‐resolved spectral measurements.